Synthesis and reduction reaction of novel triazole compounds in the solid-media condition by using microwave method - Ozil, Musa; Mentese, Emre; Kahveci, Bahittin (European Journal of Chemistry, 2012)
Some new triazole-3-one compounds have been synthesized and then reduction of carbonyl group in the molecule has been carried out to give a corresponding hydroxyl group which possesses asymmetric carbon atom in good yields, short reaction times and an eco-friendly approach in solvent-free condition by using microwave irradiation.